Efforts to Instill Character Education in Students in the Digital Era - Nadila Juanda; Najwa Az-Zahra; Chanifudin (Jurnal Pengetahuan dan Pendidikan, 2025)
Character education is a crucial aspect in shaping ethical, responsible, and socially aware individuals within society. In today’s digital era, the process of instilling character education has become increasingly complex due to rapid technological advancements that significantly influence students’ behavior, learning patterns, and social interactions. Digital technology has transformed the educational landscape by providing easier access to information and new learning opportunities, but it has also introduced challenges such as excessive use of social media, exposure to negative or inappropriate content, declining interpersonal communication, and shifts in moral values among students.This article discusses various efforts to strengthen character education among students in the digital era. The discussion covers the fundamental concept of character education as an essential component of holistic education, the challenges posed by the digital age, and effective strategies for character development. The strategies emphasized include moral knowing, which focuses on providing students with an understanding of moral values; moral loving, which aims to develop emotional attachment and care toward those values; and moral acting, which encourages the consistent practice of character values in daily life.In addition, this article explores the role of educators in implementing character education through exemplary behavior, limiting students’ excessive indulgence in digital activities, fostering positive teacher–student relationships, applying learning methods suited to students’ needs, and monitoring students’ social and digital environments. The analysis employs a descriptive analysis technique to provide a comprehensive understanding of character education implementation in the digital era